Epilogue — The ICC on the yellow brick road - Coco, A; Cross, M (Oxford University Press, 2017)
The International Criminal Court (ICC) is experiencing a phase of its life where restless weariness and even perhaps a touch of disillusionment pair with the necessity to continue walking on the path open ahead, in the hope of eventually finding the solution to its problems. These problems have been many, including alleged selectivity of action, perceived bias, lack of resources, inefficient use of available resources, lack of cooperation and accusations of political subservience.